Color-discrimination threshold determination using pseudoisochromatic test plates - Jurasevska, Kaiva; Ozolinsh, Maris; Fomins, Sergejs; Gutmane, Ausma; Zutere, Brigita; Pausus, Anete; Karitans, Varis (Frontiers in Psychology, 2014)
We produced a set of pseudoisochromatic plates for determining individual color-difference thresholds to assess test performance and test properties, and analyzed the results. We report a high test validity and classification ability for the deficiency type and severity level (comparable to that of the fourth edition of the Hardy–Rand–Rittler (HRR) test). We discuss changes of the acceptable chromatic shifts from the protan and deutan confusion lines along the CIE xy diagram, and the high correlation of individual color-difference thresholds and the red–green discrimination index. Color vision was tested using an Oculus HMC anomaloscope, a Farnsworth D15, and an HRR test on 273 schoolchildren, and 57 other subjects with previously diagnosed red–green color-vision deficiency.